Gesture friendly interfaces for classroom teaching with thinking tools - Chen, Stephen (2006)
Thinking tools are typically designed for students working on their own computers. When used from the front of a classroom, the complex graphical user interfaces of these tools can interfere with an instructor’s ability to lecture effectively and to use natural gestures. A thinking tool for the grade 9 mathematics topic of “relationships” has been developed with a more gesture-friendly interface. This gesture-friendly interface allows a teacher to focus more on interacting with students, creating engaging visualizations, and using natural hand and arm gestures as part of the lecture.